Lucille Davidson

## Answered question

2021-12-27

To solve: ${x}^{2}-6x=x\left(8+x\right)$

### Answer & Explanation

Jimmy Macias

Beginner2021-12-28Added 30 answers

Calculation:
By distributive property,
$x\left(8+x\right)=x\cdot 8+x\cdot x$
$x\left(8+x\right)=8x+{x}^{2}$
Replace
${x}^{2}-6x=8x+{x}^{2}$
Add $-{x}^{2}-8x$ on both sides,
${x}^{2}-6x-{x}^{2}-8x=8x+{x}^{2}-{x}^{2}-8x$
Add the like terms,
$0{x}^{2}-14x=0{x}^{2}+0x$
$-14x=0$
$x=0$
The value of x is 0.

Dabanka4v

Beginner2021-12-29Added 36 answers

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:
${x}^{2}-6\cdot x-\left(x\cdot \left(8+x\right)\right)=0$
$\left(\left({x}^{2}\right)-6x\right)-x\cdot \left(x+8\right)=0$
$-14x=0$
Multiply both sides of the equation by (-1): $14x=0$
Divide both sides of the equation by 14:
$x=0$

karton

Expert2022-01-09Added 613 answers

Use the distributive property to multiply x by 8+x
${x}^{2}-6x=8x+{x}^{2}$
Subtract 8x from both sides.
${x}^{2}-6x-8x={x}^{2}$
Combine to get -14x.
${x}^{2}-14x={x}^{2}$
Subtract ${x}^{2}$ from both sides.
${x}^{2}-14x-{x}^{2}=0$
Combine to get 0.
-14x=0
Product of two numbers is equal to 0 if at least one of them is 0. Since -14 is not equal to 0, x must be equal to 0.
x=0

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?